Relationship between Helicobacter pylori and glycated hemoglobin: a cohort study - Chen, Yi; Yang, Chaoyu; You, Ningning; Zhang, Jinshun (Frontiers in Cellular and Infection Microbiology, 2023)
Background Helicobacter pylori (H. pylori) has increasingly been shown to be related to extragastric diseases. Glycated hemoglobin A1c (HbA1c), an indicator of glycemic control, is closely linked to the event of diabetes. The purpose of this research was to analyze the association between H. pylori and HbA1c through a cohort study. Methods The population who underwent multiple physical checkups in the physical examination center of Taizhou Hospital was included. All of them underwent urea breath test, serological examination and physical parameter measurement. Multiple regression was used for analyzing the influencing factors of HbA1c. In addition, the result of HbA1c on H. pylori infection was studied by restricted cubic spline (RCS) analysis. The triglyceride glucose (TyG) index represents the level of insulin resistance (IR) in the population. The population was classified on the basis of primary and last H. pylori infection, therefore, the variations of HbA1c and TyG index among totally different teams were investigated. Results Multiple regression demonstrated that H. pylori was an influential factor in HbA1c. RCS analysis showed a nonlinear relationship between HbA1c and H. pylori infection. When HbA1c>5.7%, the chance of H. pylori infection was considerably enlarged. Additionally, long-term H. pylori infection increased HbA1c levels, while HbA1c levels decreased after H. pylori eradication. Similarly, long-term H. pylori infection also increased the TyG index. Conclusion Prediabetes increases the danger of H. pylori infection, long-term H. pylori infection increases HbA1c and IR levels, and wipeout of H. pylori could have a positive impact for glycemic control in the population.